Silicic, high- to extremely high-grade ignimbrites and associated deposits from the Paraná Magmatic Province, southern Brazil - Luchetti, Ana Carolina F. [UNESP]; Nardy, Antonio J.R. [UNESP]; Madeira, José (Elsevier, 2018)
The Cretaceous trachydacites and dacites of Chapecó type (ATC) and dacites and rhyolites of Palmas type (ATP) make up 2.5% of the ~ 800.000 km3 of volcanic pile in the Paraná Magmatic Province (PMP), emplaced at the onset of Gondwana breakup. Together they cover extensive areas in southern Brazil, overlapping volcanic sequences of tholeiitic basalts and andesites; occasional mafic units are also found within the silicic sequence. In the central region of the PMP silicic volcanism comprises porphyritic ATC-type, trachydacite high-grade ignimbrites (strongly welded) overlying aphyric ATP-type, rhyolite high- to extremely high-grade ignimbrites (strongly welded to lava-like). In the southwestern region strongly welded to lava-like high-grade ignimbrites overlie ATP lava domes, while in the southeast lava domes are found intercalated within the ignimbrite sequence. Characteristics of these ignimbrites are: widespread sheet-like deposits (tens to hundreds of km across); absence of basal breccias and basal fallout layers; ubiquitous horizontal to sub-horizontal sheet jointing; massive, structureless to horizontally banded-laminated rock bodies locally presenting flow folding; thoroughly homogeneous vitrophyres or with flow banding-lamination; phenocryst abundance presenting upward and lateral decrease; welded glass blobs in an ‘eutaxitic’-like texture; negligible phenocryst breakage; vitroclastic texture locally preserved; scarcity of lithic fragments. These features, combined with high eruption temperatures (≥ 1000 °C), low water content (≤ 2%) and low viscosities (104–7 Pa s) suggest that the eruptions were characterized by low fountaining, little heat loss during collapse, and high mass fluxes producing extensive deposits.
Keywords: High-grade ignimbrites; Low explosivity eruptions; Paraná Magmatic Province; Silicic volcanism